Intelligent transportation system based on image processing - Liu, Yizhe (Nanyang Technological University, 2022)
In today’s global digital world, traffic congestion is becoming a serious problem. Previous studies have provided several systems which are being used to handle traffic problems. However, each of them has its own disadvantages. In contrast, a system based on image processing is better for users. It is because this system uses image processing algorithms to get accurate data, which is more convenient and costs less to be implemented.